2017
DOI: 10.1063/1.4973218
|View full text |Cite
|
Sign up to set email alerts
|

Unique heating curves generated by radiofrequency electric-field interactions with semi-aqueous solutions

Abstract: Aqueous and nanoparticle-based solutions have been reported to heat when exposed to an alternating radiofrequency (RF) electric-field. Although the theoretical models have been developed to accurately model such a behavior given the solution composition as well as the geometrical constraints of the sample holder, these models have not been investigated across a wide-range of solutions where the dielectric properties differ, especially with regard to the real permittivity. In this work, we investigate the RF he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…We have previously shown that C 60 derivatives can be used as convenient scaffolds for anticancer therapeutic drug delivery [11], and that such agents preferentially localize in both the intracellular nuclear pore complex [12] and tumor vasculature [13]. Other applications investigated in our labs include the use of C 60 derivatives to enhance noninvasive radiofrequency cancer therapy [14][15][16] and to serve as efficacious MRI contrast agents [17][18][19].…”
mentioning
confidence: 99%
“…We have previously shown that C 60 derivatives can be used as convenient scaffolds for anticancer therapeutic drug delivery [11], and that such agents preferentially localize in both the intracellular nuclear pore complex [12] and tumor vasculature [13]. Other applications investigated in our labs include the use of C 60 derivatives to enhance noninvasive radiofrequency cancer therapy [14][15][16] and to serve as efficacious MRI contrast agents [17][18][19].…”
mentioning
confidence: 99%